2023
DOI: 10.3390/rs15245774
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Response Assessment of Land Cover Change in a Peruvian Amazonian Basin Impacted by Deforestation Using the SWAT Model

Karla Paiva,
Pedro Rau,
Cristian Montesinos
et al.

Abstract: The watershed hydrologic conditions in the Madre de Dios (MDD) Basin in the Peruvian Amazon have been irreversibly impacted by deforestation and changes in land cover. These changes have also had detrimental effects on the geomorphology, water quality, and aquatic habitat within the basin. However, there is a scarcity of hydrological modeling studies in this area, primarily due to the limited availability of hydrometeorological data. The primary objective of this study was to examine how deforestation impacts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that deforestation significantly reduces precipitation and ET (Costa and Foley, 2000;Nóbrega, 2014;Santos et al, 2017;Saddique et al, 2020). Other works carried out in the Amazon Forest highlight the impact of vegetation cover changes on the water balance (Pongratz et al, 2006;Hayhoe et al, 2011;Griffiths et al, 2018;Cabral Júnior et al, 2022) and actual ET (Souza et al, 2019;Kohler et al, 2021;Paiva et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that deforestation significantly reduces precipitation and ET (Costa and Foley, 2000;Nóbrega, 2014;Santos et al, 2017;Saddique et al, 2020). Other works carried out in the Amazon Forest highlight the impact of vegetation cover changes on the water balance (Pongratz et al, 2006;Hayhoe et al, 2011;Griffiths et al, 2018;Cabral Júnior et al, 2022) and actual ET (Souza et al, 2019;Kohler et al, 2021;Paiva et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Brasil Revealed Report produced by MapBiomas (2022), out of the 44.5 million hectares deforested on a large scale, primarily along the margins of the remaining Amazon Forest, about 13.6% were converted to agricultural land and 86.3% into pastures. In this context, it is clear that deforestation causes a decrease in ET rates, especially during the dry season (Caioni, 2021;Zhang et al, 2022;Paiva et al, 2023).…”
Section: Introductionmentioning
confidence: 99%